2020
DOI: 10.3390/ma13163461
|View full text |Cite
|
Sign up to set email alerts
|

Temperature Threshold Values of Bone Necrosis for Thermo-Explantation of Dental Implants—A Systematic Review on Preclinical In Vivo Research

Abstract: Purpose: Very high or low temperatures will lead to bone damage. The objective of this review was to analyze threshold values for thermal bone necrosis. Methods: Histological animal studies evaluating thermal effects on bone necrosis were selected via electronic and hand searches in English and German language journals until 1 November 2019. The outcome measures were temperature-exposure intervals and laser settings effecting bone damage. Furthermore, investigated parameters were the bone-to-implant contact ra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
20
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 26 publications
(23 citation statements)
references
References 45 publications
3
20
0
Order By: Relevance
“…Such results may fluctuate if different bone models are used and if different types of implant systems are used due to differences in the reaction of the laser by the surface form (32) . In some studies, bone injury by heat induction was carried out in rabbits causing adverse effects on living bone when the temperature rised above 47°C for 60 s affecting the ability of bone to regenerate (27,33,34) . The overheating at the bone-implant interface may cause bone death and compromise the bone's ability to stay alive as a differentiated tissue (35) .…”
Section: Discussionmentioning
confidence: 99%
“…Such results may fluctuate if different bone models are used and if different types of implant systems are used due to differences in the reaction of the laser by the surface form (32) . In some studies, bone injury by heat induction was carried out in rabbits causing adverse effects on living bone when the temperature rised above 47°C for 60 s affecting the ability of bone to regenerate (27,33,34) . The overheating at the bone-implant interface may cause bone death and compromise the bone's ability to stay alive as a differentiated tissue (35) .…”
Section: Discussionmentioning
confidence: 99%
“…Kniha et al stated that a thermal threshold between 47 and 55 °C might cause bone necrosis. In addition, bone density has emerged as a determinant factor, with cancellous bone more susceptible to high temperatures than cortical bone [ 23 ]. However, Trisi et al reported that an increase in temperature up to 60 °C maintained for one minute during osteotomy site preparation did not show statistically significant ( p ˃ 0.05) effects on dental implant osseointegration; however, they recommended careful drilling procedures with sufficient irrigation to avoid peri-implant defects [ 24 ].…”
Section: Discussionmentioning
confidence: 99%
“…The extent of bone damage depends on the temperature and duration of its application. Application of heat between 47 • C and 55 • C for 1 min can cause irreversible bone damage [38]. Cold cryoinsults also caused osteonecrosis in an emu bone model [38,39], with the moderated critical temperature of 3.5 • C for the reduction in osteocyte viability below 50%.…”
Section: Introductionmentioning
confidence: 99%
“…Application of heat between 47 • C and 55 • C for 1 min can cause irreversible bone damage [38]. Cold cryoinsults also caused osteonecrosis in an emu bone model [38,39], with the moderated critical temperature of 3.5 • C for the reduction in osteocyte viability below 50%. The holding time and the rate of temperature change were not considered in the study [39].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation